'Climate Change as a Spice': Brokering Environmental Knowledge in Bangladesh's Development Industry. Issue 3 (27th May 2022) - Dewan, Camelia
ABSTRACT: This article examines whether the use of climate change as a 'spice' in order to attract donor funding may instead exacerbate existing environmental problems. The World Bank's latest adaptation project in coastal Bangladesh aims to create higher and wider embankments against rising sea levels. This disregards a long history of how embankments, by stopping beneficial monsoon inundations, result in dying rivers and damaging floods that devastate rural livelihoods. Bangladeshi 'development brokers' must therefore balance their roles as project employees supporting embankments as adaptation, and as locals knowledgeable about their harmful effects. The article shows how donors, NGOs, consultants and government bodies with different agendas, priorities and knowledge backgrounds 'translate' climate change to legitimise their activities. It contributes to debates about the politics of environmental knowledge production by arguing that development brokerage helps explain why some climate adaptation projects increase environmental vulnerability, while others address local needs.